Amino-functionalized graphene oxide-supported networked Pd–Ag nanowires as highly efficient catalyst for reducing Cr(VI) in industrial effluent by formic acid. (October 2020) - Bao, Shuangyou; Liu, Hu; Liu, Yequn; Yang, Weiwei; Wang, Yingjun; Yu, Yongsheng; Sun, Yinyong; Li, Kefei
Abstract: Cr(VI) pollution in wastewater has increasingly become a global environmental problem owing to its acute toxicity. Herein, we present the one-pot procedure for preparing the amino-functionalized (-NH2 ) graphene oxide (GO-) supported networked Pd–Ag nanowires by co-reduction growth in polyol solution, which show the highly efficient catalytic performance with the excellent cycling stability for the catalytic Cr(VI) reduction by formic acid as an in-situ source of hydrogen at room temperature. The electron transfer from Ag and amino to Pd increases the electron density of Pd, which enhances the catalytic formic acid decomposition and subsequent the catalytic Cr(VI) reduction. The catalytic reduction rate constant of Pd3 Ag1 /GO-NH2 is determined to be 0.0768 min −1, which is much superior to the monometallic Pd/GO-NH2 and Pd3 Ag1 /GO. This study provides a novel strategy to develop catalysts for the catalytic reduction of Cr(VI) to Cr(III) in the industrial effluent using formic acid as an in-situ source of hydrogen. Graphical abstract: Image 1 Highlights: GO-NH2 -supported networked Pd–Ag nanowires was prepared. The electron transfer from Ag to Pd could enhance the catalytic Cr(VI) reduction. -NH2 modification of GO could enhance the catalytic Cr(VI) reduction. PdAg/GO-NH2 catalyst showed excellent catalytic activity for Cr(VI) reduction.